A multi-country mixed-method study identifying the association between perceived ethical work climate and problems among critical care nurses - Fatma Refaat Ahmed; Nabeel Al-Yateem; Farha Hisham Hijji; Ghadeer Al Dweik; Mohammad Alkawaldeh; Muhammad Arsyad Subu; Jacqueline Maria Dias; Mohannad Eid Aburuz; Sally Mohammed Farghaly (BMC, 2024)
Abstract Background Given the grave ethical tension and dilemmas posed continuously which are aggravated in the intensive care unit context and its related caregiving provision, combined with their impact on critical care nurses' job satisfaction and work-related risks, exploring and analyzing these tensions and conflicts is crucial. This study was conducted to examine the relationship between perceived ethical work climate and problems among critical care nurses in addition to exploring their perspectives on the ethical work climates while caring for patients with infectious diseases. Design and method A mixed-method research design was used to conduct this study among 635 participants, comprising 170 from Egypt, 144 from Jordan, 161 from Saudi Arabia, and 160 from the United Arab Emirates. Online or paper-based survey forms were distributed to all eligible critical care nurses who agreed to take part in the study. The survey contained both quantitative and qualitative data that were analyzed separately and integrated during the discussion. The study was reported following the STROBE guidelines. Findings The overall ethical work climate was fairly good and was significantly associated with ICU nurses' personal and professional characteristics. The findings also identified three main themes: (1) an ethical sense of failure, (2) environmental condemnation, and (3) an instant action plan for resolving ethical conflicts. Conclusions ICU nurses perceived that ICU ethical climate was fairly good. The results indicated that ICU nurses generally had a relatively fair perception of the ethical work climate, with implications for addressing ethical issues and conflicts in various settings. Impact Mentorship and/or close supervision concerning ethical resilience, consultation, and decision-making is crucial in the ICU milieu. Metacognitive strategies to reinforce problem-solving and decision-making ICU nurses' skills could help them overcome the different ethical challenges. Adequate resources, teamwork, and organizational support are promising tactics to improve ICU nurses' ethical skills. Trial registration Not applicable.